2019
DOI: 10.1108/nfs-11-2018-0309
|View full text |Cite
|
Sign up to set email alerts
|

How label and nutritional claims affect consumers’ acceptance, buying intention and quality perception toward a beverage made from cashew nut

Abstract: Purpose The purpose of this paper is to evaluate the influence of the front of a package label and the nutritional claims linked to it over consumers’ expectations as to acceptance, purchase attitude and perception of quality characteristics of a new functional beverage made from cashew nut milk and added with mango juice and prebiotic substances. Design/methodology/approach Three versions of the front label were developed, which differed just by the type of nutritional claim presented (“0 per cent lactose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(41 reference statements)
0
3
0
1
Order By: Relevance
“…Not communicating properly, the required information may influence consumers’ future expectations negatively and lead to lower purchase intention and lessening of consumer trust (Fernqvist et al , 2015). On the other hand, appropriate labels would create a positive expectation on consumers regarding the quality attributes, overall impression and buying attitude (Rebouças et al , 2019). Furthermore, the use of food quality labels is suggested to bring benefits to consumers as well as producers, because these latter would buy a product with specific value-adding qualities and producers could better promote food products with unique quality (Sadílek, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Not communicating properly, the required information may influence consumers’ future expectations negatively and lead to lower purchase intention and lessening of consumer trust (Fernqvist et al , 2015). On the other hand, appropriate labels would create a positive expectation on consumers regarding the quality attributes, overall impression and buying attitude (Rebouças et al , 2019). Furthermore, the use of food quality labels is suggested to bring benefits to consumers as well as producers, because these latter would buy a product with specific value-adding qualities and producers could better promote food products with unique quality (Sadílek, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Duran et al (2019) evaluated 3491 foods and beverages in Brazil and observed that the products that contained the most nutritional claims were also the ones with the highest amount of nutrients of public health concern in their composition. Moreover, several studies have demonstrated that the presence of nutritional claims in foods can generate positive associations and influence the perception of healthiness, consumer choice and purchase decisions (Bialkova et al , 2016; Loebnitz and Grunert, 2018; Nobrega et al , 2020; Pinto et al , 2017; Rebouças et al , 2019). Labiner-Wolfe et al (2010) evaluated the effect of low-carb claims on the perceptions of 4,320 consumers from the USA about health and the contribution of these foods to weight control online by displaying images on food labels.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, alegações nutricionais em geral têm a capacidade de influenciar a percepção de saudabilidade, escolha e compra dos consumidores [38][39][40][41][42] . Segundo Williams 43 , por exemplo, a presença de alegações nutricionais e de saúde nos rótulos de alimentos pode desestimular alguns consumidores a procurar por mais informações nutricionais na embalagem.…”
Section: /13unclassified